ARTIFICIAL INTELLIGENCE FOR MODELING MATERIALS WITH SPECIFICED PROPERTIES - Матченко, Т. І. (Proceedings of National Aviation University (archive), 2021)
The block diagrams of formation of the purpose of research, construction of criteria of change of a qualitative condition, structural model of damage and modeling of technological progress are offered.